Channel crossings: offshoring asylum and the afterlife of empire in the Dover Strait. Issue 13 (21st October 2021) - Davies, Thom; Isakjee, Arshad; Mayblin, Lucy; Turner, Joe
ABSTRACT: In 2020, over 8, 400 people made their way from France to the UK coast using small vessels. They did so principally in order to claim asylum in the United Kingdom (UK). Much like in other border-zones, the UK state has portrayed irregular Channel crossings as an invading threat and has deployed a militarized response. While there is burgeoning scholarship focusing on informal migrant camps in the Calais area, there has been little analysis of state responses to irregular Channel crossings. This article begins to address this gap, situating contemporary British responses to irregular Channel crossers within the context of colonial histories and maritime legacies. We focus particularly on the enduring appeal of "the offshore" as a place where undesirable racialized populations can be placed. Our aim is to offer a historicized perspective on this phenomenon which seeks to respond to calls to embed colonial histories in analyses of the present.